Is artificial intelligence an opportunity or a threat in nursing care?: An in-depth phenomenological study - ALKAN, Seval AĞAÇDİKEN; KIRMACI, Neslihan DUMAN; KOÇ, Zeliha (Elsevier BV, 2025)
In the contemporary landscape, the use of artificial intelligence (AI) in nursing care has sparked ongoing debates regarding its merits and drawbacks.This study endeavored to elucidate the perceptions of nurses regarding whether AI should be construed as an opportunity or a threat in the context of patient care delivery.A qualitative, descriptive, phenomenological design was used. The study was conducted at a university hospital from December 15, 2023, to January 1, 2024. Employing a purposive sampling method, the study achieved data saturation after interviews with 13 nurses. Qualitative data were gathered using a semi-structured interview form, and content analysis was conducted following the procedural steps outlined in Colaizzi's phenomenological data analysis.In the course of the study, four distinct categories emerged: "Nursing Care Practices", "Diagnosis and Treatment Processes", "Management in Nursing", and "Nursing Education and Research". Within the category of "Nursing Care Practices", a detailed examination revealed three overarching themes, each encompassing 15 sub-themes. These themes were "ethical and legal dimensions", "positive thoughts", and "negative thoughts".This study reveals that the nurses believed that "AI can support, facilitate, and enhance nursing care when implemented within defined parameters and under appropriate oversight." The same participants conceptualized AI as a positive tool that augments clinical decision-making processes. These findings suggest that the integration of AI, when guided by ethical considerations and patient safety protocols, is a promising avenue for advancing the delivery of nursing care.
Keywords: Male; Adult; Artificial Intelligence; Attitude of Health Personnel; Humans; Nursing Care; Female; Middle Aged; Nursing Staff, Hospital; Qualitative Research